Folks from Dixie - Dunbar, Paul Laurence, 1872-1906; Kemble, E. W. (Edward Windsor), 1861-1933 (Salt Lake City, UT : Project Gutenberg, 2024)
"Folks from Dixie" by Paul Laurence Dunbar is a collection of stories written in the late 19th century. This work captures the experiences and emotions of African American individuals in the South, often exploring themes of love, faith, and the social dynamics of plantation life. The opening portion highlights the character of Anner 'Lizer, a belle of the plantation, and her relationship with Sam Merritt, illustrating the challenges they face amidst the backdrop of religious fervor and personal aspirations. At the start of the book, we are introduced to Anner 'Lizer, described as the most beautiful woman on the Selfridge estate, who is romantically involved with Sam Merritt. Their relationship is complicated by Anner 'Lizer's deepening religious conviction, which begins to create a rift between her and Sam, who remains indifferent to the church gatherings that she cherishes. The tension escalates as Anner 'Lizer grapples with her desire for spiritual fulfillment while longing for Sam's companionship. Ultimately, she realizes that her feelings for him are a stumbling block on her path to salvation, setting the stage for a personal conflict between love and faith. This opening sets up not only the character dynamics but also the cultural and spiritual struggles within the African American community during the era. (This is an automatically generated summary.)
Anner 'Lizer's stumblin' block -- The ordeal at Mt. Hope -- The colonel's awakening -- The trial sermons on Bull-Skin -- Jimsella -- Mt. Pisgah's Christmas 'possum -- A family feud -- Aunt Mandy's investment -- The intervention of Peter -- Nelse Hatton's vengeance -- At Shaft 11 -- The deliberation of Mr. Dunkin.
Release date is 2024-12-29
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Short stories, American; African Americans -- Fiction; Southern States -- Social life and customs -- Fiction